Avaliação do projeto de extensão CLAC (Cursos de Línguas Abertos à Comunidade/Faculdade de Letras/UFRJ) como uma ação para a formação docente - Sousa, Franciane Santos de (2019)
This study aimed at evaluating the role of the Project called “Language Courses Open to community” (CLAC), an extension activity of the Faculty of Language and Literature of the Federal University of Rio de Janeiro (UFRJ), as an action of teachers’ initial and continued training for the teaching of languages. Our objective was to evaluate the project’s contribution at the point of view of the courses’ ex-monitors (students and ex-students from the Language and Literature undergraduate course at UFRJ) and their supervisors (teachers from the Faculty of Language and Literature). For attaining our objective, we used an objective-oriented evaluative approach aiming at establishing a relationship between the data obtained by the study and the objectives of the CLAC project, aiming to find out how much the project contributed or continues contributing to the teachers’ training of the ones interviewed. Data collection was carried by use of a bibliographical and documentary research, an interview, a focus group, a field observation and questionnaires. Such questionnaires, whose design was based on the set of categories and indicators of this evaluation, were specifically used to fulfill the objective of the present study and to answer its evaluation questions. The interviewees were divided into three groups, namely: group 1, composed of language monitors who graduated from 2012 to 2017; group 2, made of teachers from the Faculty of Language and Literature of UFRJ who were previously CLAC language monitors; and group 3, formed from CLAC supervisors. For the quantitative data, we used a statistical and descriptive analysis and for the qualitative analysis of the answers given to the open questions we conducted a content analysis. The results fulfilled the purpose of the study and answered its evaluation questions, so that CLAC stood out as a very important project of teachers’ training for graduates from the Faculty of Language and Literature of UFRJ, mainly because it made it possible for those graduates to act as teachers and to do that with academic supervision. Although its contributions were generally very well evaluated, the project presented some weak aspects: the accessibility issue has not been addressed in a satisfactory way; and the uneven treatment given to the stages of research development which devotes more attention to its theoretical part but does not deal with the publication of studies with the same dedication.